Veivosaki-yaga: a culturally appropriate Indigenous research method in Fiji. Issue 6 (3rd July 2018) - Tagicakiverata, Isimeli Waibuta; Nilan, Pam
Abstract: This article reports on the development of a new culturally sensitive approach to collecting group discussion data in the Pacific: veivosaki-yaga . The new approach was developed during a project on Technical and Vocational Education (TVET) in multicultural Fiji. One challenge was to gain understanding from villages of parental attitudes towards TVET. While focus groups proved to answer the purpose for Indian Fijian parents, they were deemed culturally inappropriate for Indigenous Fijian parents. As a 'de-colonising' Pacific methodology, veivosaki-yaga was judged to offer a culturally appropriate framework. Arising from strategic communication conventions in Indigenous Fijian culture, veivosaki-yaga means 'worthwhile discussion' – of serious topics. It differs from the now well-known Pacific methodology approach of talanoa, which is based on much more informal and free-flowing discussion. This paper does not engage the findings of the original project as such, but seeks to convey the value of a culturally appropriate methodological approach devised therein. It contributes to the currently evolving literature on Pacific methodologies in the field of qualitative educational research.